Agricultural Distortions in Sub-Saharan Africa : Trade and Welfare Indicators, 1961 to 2004 - Croser, Johanna; Anderson, Kym (2012)
For decades, agricultural price and trade policies in Sub-Saharan Africa have hampered farmers contributions to economic growth and poverty reduction. Although there has been much policy reform over the past two decades, the injections of agricultural development funding, together with ongoing regional and global trade negotiations, have brought distortionary policies under the spotlight once again. A key question asked of those policies is: How much are they still reducing national economic welfare and trade? Economy-wide models are able to address that question, but they are not available for many poor countries. Even where they are, typically they apply to just one particular previous year and so are unable to provide trends in effects over time. This paper provides a partial-equilibrium alternative to economy-wide modeling, by drawing on a modification of so-called trade restrictiveness indexes to provide theoretically precise indicators of the trade and welfare effects of agricultural policy distortions to producer and consumer prices over the past half-century. The authors generate time series of country level indexes, as well as Africa-wide aggregates. They also provide annual commodity market indexes for the region, and a sense of the relative importance of the key policy instruments used.